Manajemen Sumber Daya Manusia Pendidikan di SDIT Al Hikam Banyudono Boyolali - Az Zahra, Khofifah; Mighfar, Shokhibul; Puspitasari, Veronicca; Munadi, Muhammad (Jurnal Al-Ilmu: Jurnal Penelitian dan Pendidikan Madrasah Ibtidaiyah, 2025)
The purpose of this study was to determine the recruitment and selection process as well as training, development and performance assessment, as well as compensation and protection of teaching and education personnel at SDIT Al-Hikam Banyudono. The method used was descriptive qualitative. Data collection techniques used observation, interviews and document studies. The results showed that the teacher recruitment process has been carried out with various processes. This recruitment activity begins with planning teacher needs, announcing teacher vacancies, requirements that must be met by prospective teachers, selection with various tests, and determining teacher acceptance. Training, development and achievement assessment can be seen through productivity, employee performance, organizational culture, morale and image of the institution, etc. In addition, employees also get some compensation and protection such as: family, health, child, evening hours, and class teacher allowances as well as DPLK and meal allowances. However, this is still the gross salary. While the net salary will experience deductions for delays, cooperatives, UPZIZ, DPLK, IKK, and IKM. From these funds, in the end, is the salary received.